s-Block Metal-Lanthanide Bonding: Direct Comparison of Mg-Yb and Mg-Ca Complexes - Thakur, Sandeep Kumar; Roig, Nil; Maurer, Johannes; Langer, Jens; Alonso, Mercedes; Harder, Sjoerd (Journal of the American Chemical Society, 2025)
Despite considerable progress in understanding the fundamental aspects of metal-metal bonding, lanthanide-metal bonding is limited to interactions between lanthanide (Ln) metals and electron-rich p- or d-block metals. Exemplified by a Mg-Yb complex, we present synthesis and extensive computational analyses of the first s-block metal-Ln bond. Key to its formation is the unique Mg0 complex [(BDI*)MgNa]2 (1) which can be viewed as a dimer consisting of two magnesyl anions, (BDI*)Mg-, bridged by two Na+ cations (BDI* = HC[C(tBu)N-DIPeP]2, DIPeP = 2,6-CHEt2-phenyl). Reaction of dimeric 1 with (YbN’’2)2 (N’’ = N(SiMe3)2) quantitatively gave the mixed complex [(BDI*)MgNa/YbN’’2] (2-Yb) in which (BDI*)Mg- anions bridge between Yb2+ and Na+ cations (Mg-Yb: 3.466(1), Mg-Na: 3.415(1) Å). Atoms-In-Molecules shows Mg-Yb and Mg-Na bond paths corresponding to weak electrostatic interactions. Complex 2-Yb is isostructural to previously reported [(BDI*)MgNa/CaN’’2] (2-Ca). Weak Mg0-M2+ (M = Ca, Yb) bonding is supported by facile exchange reactions with (SrN’’2)2 leading to formation of [(BDI*)MgNa/SrN’’2] (2-Sr). Energy decomposition analysis (EDA-NOCV) confirmed major electrostatic Mg0-M2+ bonding (63-66%), while orbital interactions are less significant (19-20%). Both, 2-Ca and 2-Yb show considerable Mg0 → M2+ electron transfer leading to oxidation-state ambiguities (Mg0-M+II ↔ Mg+I-M+I). Effective-Oxidation-State calculations assign the following metal oxidation states, Na+I-Mg0-M+II, with a reliability index of 69-72%. Despite structural and electronic similarities, there are differences in reactivities. Complex 2-Ca reacts only as a 2-electron reducing agent whereas 2-Yb can deliver up to three electrons. This study includes reactions with N2O, TEMPO, and Me3PX (X = O, S, Se). While only 2-Ca could be converted in a complex with incorporated O2-, complexes with S2- or Se2- have been isolated for both.
CRIS-Team Scopus Importer:2025-04-18

Similarities and Differences in Benzene Reduction with Ca, Sr, Yb and Sm: Strong Evidence for Tetra-Anionic Benzene - Thakur, Sandeep Kumar; Roig, Nil; Monreal-Corona, Roger; Langer, Jens; Alonso, Mercedes; Harder, Sjoerd (Angewandte Chemie International Edition, 2024)
Inverse sandwich complexes of Yb and Sm stabilized by a bulky β-diketiminate (BDI) ligand have been prepared: (BDI)Ln(η6,η6-C6H6)Ln(BDI); Ln=lanthanide. Coordinated benzene ligands can be neutral, di-anionic or, often controversially discussed, even tetra-anionic. The formal charge on benzene is correlated to assignment of the metal oxidation state which generally poses a problem. Herein, we take advantage of the structural similarities found when comparing CaII with YbII, and SrII with SmII complexes. In this work, we found an excellent overlap of the Ca/Yb inverse sandwich structures but a striking difference for the Sr/Sm pair. The much shorter Sm−N and Sm-C6H6 distances are strong evidence for a SmIII-benzene−4-SmIII assignment. This was further supported by NMR spectroscopy, magnetic susceptibility, reactivity and comprehensive computational investigation.
CRIS-Team Scopus Importer:2024-05-24
Keywords: Aromaticity; Benzene; Reduction; Samarium; Ytterbium